Dermal exosomes containing miR-218-5p promote hair regeneration by regulating β-catenin signaling - Hu, Shiqi (Sci Adv, 2020)
The progression in the hair follicle cycle from the telogen to the anagen phase is the key to regulating hair regrowth. Dermal papilla (DP) cells support hair growth and regulate the hair cycle. However, they gradually lose key inductive properties upon culture. DP cells can partially restore their capacity to promote hair regrowth after being subjected to spheroid culture. In this study, results revealed that DP spheroids are effective at inducing the progression of the hair follicle cycle from telogen to anagen compared with just DP cell or minoxidil treatment. Because of the importance of paracrine signaling in this process, secretome and exosomes were isolated from DP cell culture, and their therapeutic efficacies were investigated. We demonstrated that miR-218-5p was notably up-regulated in DP spheroid–derived exosomes. Western blot and immunofluorescence imaging were used to demonstrate that DP spheroid–derived exosomes up-regulated β-catenin, promoting the development of hair follicles.